Development of Android-Based Management Information System Application for Student Final Project Services - Ghani, Mukhammad Rivaldi; Donoriyanto, Dwi Sukma (P3M Politeknik Negeri Bengkalis, 2025)
The final project service system in the Industrial Engineering Study Program at Universitas Pembangunan Nasional